Розмір відео: 1280 X 720853 X 480640 X 360
Показувати елементи керування програвачем
Автоматичне відтворення
Автоповтор
Where was the tricky part? Did I miss something ?
I solved it too. It wasn't tricky at all.
Quoting Sherlock Holmes "Elementary Watson".10 min explanation not needed tor this
He talks too damn much.
Please using complex analysis method sir.
This gives rise to a quadratic equation, therefore x=a+root b, y=a-root b. From the first equation follows a=3. Then from the second it follows b=3.
First it is simple,but it is become complicated,
very nice sir
bro 7th grades could do this
I thought this was the most basic of product of roots and sum of roots problem.
awesome
The key step is y=6/x or x=6/y
This guy is the king of generating hate in his comment section 😂
can't you just start this thing "x + y = xy" and skip a bunch of steps?
x=6-y put in equation 2 => y²-6y+6=0 => y1,2 = 3 +/- Sqrt(3). Since y and y are interchangable x1,2 =3 -/+ SQRT(3).Where's the tricky part?
(3)+(3) =6 (y ➖ 3x+3). (xy ➖ 3xy+2) .
Do you think you can do some collage level stuff? This is NOT higher math 😱
😮😮
X= 3+ root3, Y= 3- root3
Ingerchangeable so there are 2 sets of solutioms
@@joss5515 yes
No, the other solution is extraneous
That is not higher math.
x+y=6 , x*y=6 , x=6/y , 6/y+y=6 , y^2-6y+6=0 , y= 3+V3 , 3-V3 , x=6-y , x=6-(3+V3) , x=3-V3 , x=6-(3-V3) , x=3+V3 , solu (x , y ) , (3-V3 , 3+V3) , (3+V3 , 3+V3) , test , x*y=6 , (3-V3) * (3+V3) = 9-3*V3+3*V3-3 , --> 6 , (3-V3) * (3+V3) = 9+3*V3-3*V3-3 , --> 6 , OK ,
Bot bad Mr
Speak slowly
Where was the tricky part? Did I miss something ?
I solved it too. It wasn't tricky at all.
Quoting Sherlock Holmes "Elementary Watson".
10 min explanation not needed tor this
He talks too damn much.
Please using complex analysis method sir.
This gives rise to a quadratic equation, therefore x=a+root b, y=a-root b. From the first equation follows a=3. Then from the second it follows b=3.
First it is simple,but it is become complicated,
very nice sir
bro 7th grades could do this
I thought this was the most basic of product of roots and sum of roots problem.
awesome
The key step is y=6/x or x=6/y
This guy is the king of generating hate in his comment section 😂
can't you just start this thing "x + y = xy" and skip a bunch of steps?
x=6-y put in equation 2 => y²-6y+6=0 => y1,2 = 3 +/- Sqrt(3). Since y and y are interchangable x1,2 =3 -/+ SQRT(3).
Where's the tricky part?
(3)+(3) =6 (y ➖ 3x+3). (xy ➖ 3xy+2) .
Do you think you can do some collage level stuff? This is NOT higher math 😱
😮😮
X= 3+ root3, Y= 3- root3
Ingerchangeable so there are 2 sets of solutioms
@@joss5515 yes
No, the other solution is extraneous
That is not higher math.
x+y=6 , x*y=6 , x=6/y , 6/y+y=6 , y^2-6y+6=0 , y= 3+V3 , 3-V3 , x=6-y , x=6-(3+V3) , x=3-V3 ,
x=6-(3-V3) , x=3+V3 , solu (x , y ) , (3-V3 , 3+V3) , (3+V3 , 3+V3) ,
test , x*y=6 , (3-V3) * (3+V3) = 9-3*V3+3*V3-3 , --> 6 , (3-V3) * (3+V3) = 9+3*V3-3*V3-3 , --> 6 , OK ,
Bot bad Mr
Speak slowly